2006
DOI: 10.1038/sj.onc.1210102
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of docetaxel cytotoxicity in breast cancer cells: uncoupling of aberrant mitosis and apoptosis

Abstract: Among microtubule-targeting agents, docetaxel has received recent interest owing to its good therapeutic index. Clinical trials have underlined its potential for the treatment of advanced breast cancer, although little is known about its molecular mode of action in this context. We characterized the molecular changes induced by docetaxel in two well-known human breast carcinoma cell lines. Two mechanisms of action according to drug concentration were suggested by a biphasic sensitivity curve, and were further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
111
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(137 citation statements)
references
References 30 publications
23
111
1
Order By: Relevance
“…Although the cell-cycle profiles were largely similar for each cell line treated with ixabepilone or paclitaxel, the P-gp-expressing DU4475 and MDA-MB-231 (F 11 ) PTX-r cells were more sensitive to ixabepilone. Consistent with previous reports, the cell-death response observed at lower concentrations of MTAs was likely driven by a transient mitotic arrest and not a sustained mitotic arrest (27).…”
Section: Resultssupporting
confidence: 79%
“…Although the cell-cycle profiles were largely similar for each cell line treated with ixabepilone or paclitaxel, the P-gp-expressing DU4475 and MDA-MB-231 (F 11 ) PTX-r cells were more sensitive to ixabepilone. Consistent with previous reports, the cell-death response observed at lower concentrations of MTAs was likely driven by a transient mitotic arrest and not a sustained mitotic arrest (27).…”
Section: Resultssupporting
confidence: 79%
“…No long-lasting cell cycle arrest in MCF7 cells exposed to low dose of DTX was observed, and DNA content was reduced but to a lesser extend than at high dose, without significant cell death in attached cells at 72 h. These findings are in agreement with literature reports. Low dose of DTX was shown to induce aberrant mitosis followed by aneuploidy and necrosis, whereas high dose induced mitotic arrest followed by mitotic slippage into tetraploid or ''pseudo-G1'' phase then apoptosis [10,26]. Our DNA content measurements, reflecting cell proliferation and DNA ploidy although consistent with literature, underestimated antiproliferative effects of DTX at high dose because of cell tetraploidy.…”
Section: Discussionsupporting
confidence: 73%
“…At low concentration (10 nM), DTX was shown to activate diacylglycerol (DAG) kinase, a lipid kinase that phosphorylates DAG into phosphatidic acid (PA) [18]. Recently, the dose dependence of the response of human breast carcinoma cells to DTX has been reported [10]. Like paclitaxel [19], DTX provoked striking differences in cell cycle according to the dose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Docetaxel suppresses tumor cell growth in two different modes: at high concentration, docetaxel induces G2/M cell cycle arrest and apoptosis, whereas a very low level of docetaxel causes aberrant mitosis followed by necrosis. 7,8 Although docetaxel has many advantages in cancer therapy, it can cause serious side effects, such as neutropenia, myelosuppression, anemia, and hypersensitivity reaction, which limit its clinical applications. [9][10][11] Some of these side effects are simply induced by The authors' previous work showed that docetaxel-loaded solid lipid nanoparticles (DSNs) have many advantages compared with other nanoformulations, including easier preparation, better stability, component materials safety, and controlled release.…”
Section: Introductionmentioning
confidence: 99%